Chicory inulin does not increase stool weight or speed up intestinal transit time in healthy male subjects - Slavin, Joanne; Feirtag, Joellen (Food & function, 2011)
Inulin is a non-digestible oligosaccharide classified as a prebiotic, a substrate that promotes the growth of certain beneficial microorganisms in the gut. We examined the effect of a 20 g day(-1) supplement of chicory inulin on stool weight, intestinal transit time, stool frequency and consistency, selected intestinal microorganisms and enzymes, fecal pH, short chain fatty acids and ammonia produced as by-products of bacterial fermentation. Twelve healthy male volunteers consumed a well-defined, controlled diet with and without a 20 g day(-1) supplement of chicory inulin (degree of polymerization (DP) ranging for 2-60), with each treatment lasting for 3 weeks in a randomized, double-blind crossover trial. Inulin was consumed in a low fat ice cream. No differences were found in flavor or appeal between the control and inulin-containing ice creams. Inulin consumption resulted in a significant increase in total anaerobes and Lactobacillus species and a significant decrease in ammonia levels and β-glucuronidase activity. Flatulence increased significantly with the inulin treatment. No other significant differences were found in bowel function with the addition of inulin to the diet. Thus, inulin is easily incorporated into a food product and has no negative effects on food acceptability. Twenty grams of inulin was well tolerated, but had minimal effects on measures of laxation in healthy, human subjects.